Development of low-carbon materials from GGBS and clay brick powder for 3D concrete printing. (20th June 2023) - Zhao, Yasong; Gao, Yangyunzhi; Chen, Gaofeng; Li, Shujun; Singh, Amardeep; Luo, Xu; Liu, Cheng; Gao, Jianming; Du, Hongjian
Highlights: A low-carbon binder material was developed for 3D printing from GGBS and CBP. Printability is affected comprehensively by morphology and PSD of GGBS and CBP. Printing process increases macro pores and reduces the sphericity of pores. Adding GGBS and CBP refines pores and improves chloride penetration resistance. Abstract: A new low-carbon material for 3D concrete printing by utilizing recycled ground granulated blast-furnace slag (GGBS) and clay brick powder (CBP) was developed to reduce the carbon footprint. The printability and hardened properties of 3D printed mortar were systematically investigated to reveal the coupling effect of GGBS and CBP. The results indicate that the printability of mortar is significantly influenced by the morphology and particle size distribution of admixtures. The vitreous surface of GGBS reduces the yield stress of the paste, while the porous surface of CBP has the opposite effect. Furthermore, increasing CBP replacement leads to a denser packing of binders, which releases more free water to increase the fluidity of mortar. The printing process not only increases the proportion of capillary and macro pores, but also reduces the sphericity of macro pores. As a result, 3D printed mortar experiences a 10 ∼ 50 % loss in compressive strength and mechanical anisotropy of 3D printed mortar. The secondary hydration reaction of GGBS and CBP reduces the average pore diameter from 41.7 nm to 15.3∼19.3 nm and increases the complexity of micro pores, resulting in a significant decrease in chloride ions migration in the mortar. These results demonstrate the feasibility of using low-carbon materials containing GGBS and CBP for 3D concrete printing.